Thulium laser transurethral vaporesection of the prostate versus transurethral resection of the prostate for men with lower urinary tract symptoms or urinary retention (UNBLOCS): a randomised controlled trial. Issue 10243 (4th July 2020) - Hashim, Hashim; Worthington, Jo; Abrams, Paul; Young, Grace; Taylor, Hilary; Noble, Sian M; Brookes, Sara T; Cotterill, Nikki; Page, Tobias; Swami, K Satchi; Lane, J Athene; ,
Summary: Background: Transurethral resection of the prostate (TURP) is the standard operation for benign prostatic obstruction. Thulium laser transurethral vaporesection of the prostate (ThuVARP) is a technique with suggested advantages over TURP, including reduced complications and hospital stay. We aimed to investigate TURP versus ThuVARP in men with lower urinary tract symptoms or urinary retention secondary to benign prostatic obstruction. Methods: In this randomised, blinded, parallel-group, pragmatic equivalence trial, men in seven UK hospitals with bothersome lower urinary tract symptoms or urinary retention secondary to benign prostatic obstruction were randomly assigned (1:1) at the point of surgery to receive ThuVARP or TURP. Patients were masked until follow-up completion. Centres used their usual TURP procedure (monopolar or bipolar). All trial surgeons underwent training on the ThuVARP technique. Co-primary outcomes were maximum urinary flow rate (Qmax) and International Prostate Symptom Score (IPSS) at 12-months post-surgery. Equivalence was defined as a difference of 2·5 points or less for IPSS and 4 mL per s or less for Qmax. Analysis was done according to the intention-to-treat principle. The trial is registered with the ISRCTN Registry, ISRCTN00788389. Findings: Between July 23, 2014, and Dec 30, 2016, 410 men were randomly assigned to ThuVARP or TURP, 205 per study group. TURP was superior for Qmax (mean 23·2 mL per s for TURP and 20·2 mL per s for ThuVARP; adjusted difference in means −3·12, 95% CI −5·79 to −0·45). Equivalence was shown for IPSS (mean 6·3 for TURP and 6·4 for ThuVARP; adjusted difference in means 0·28, −0·92 to 1·49). Mean hospital stay was 48 h in both study groups. 91 (45%) of 204 patients in the TURP group and 96 (47%) of 203 patients in the ThuVARP group had at least one complication. Interpretation: TURP and ThuVARP were equivalent for urinary symptom improvement (IPSS) 12-months post-surgery, and TURP was superior for Qmax. Anticipated laser benefits for ThuVARP of reduced hospital stay and complications were not observed. Funding: UK National Institute for Health Research Health Technology Assessment Programme.